2015
DOI: 10.1007/s13762-015-0766-5
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study on phosphate removal from aqueous solution by biochar derived from peanut shell as renewable adsorptive media

Abstract: As an alternative strategy for phosphate removal, biochar (black carbon) has characteristics superior to those of widely used adsorptive media, from both economic and environmental points of view. In this study, various types of biochar derived from oak wood, bamboo wood, maize residue, soybean stover, and peanut shell were tested for evaluation of phosphate removal. After 24 h of reaction time, the phosphate removal was limited (2.0-9.4 %) in case of general adsorptive media. However, interestingly, among var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(48 citation statements)
references
References 41 publications
4
44
0
Order By: Relevance
“…[43] The release of P may also occur due to low Ca content in biochar. [44,45] For biochars that do not contain abundant metal ions, it will be difficult for adsorption to occur when repulsive electrostatic forces exist. For example, Yao et al [44] tested thirteen biochars for P adsorption and found that most of them had little or no ability to adsorb P in a sandy soil.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…[43] The release of P may also occur due to low Ca content in biochar. [44,45] For biochars that do not contain abundant metal ions, it will be difficult for adsorption to occur when repulsive electrostatic forces exist. For example, Yao et al [44] tested thirteen biochars for P adsorption and found that most of them had little or no ability to adsorb P in a sandy soil.…”
Section: Fundingmentioning
confidence: 99%
“…For example, Yao et al [44] tested thirteen biochars for P adsorption and found that most of them had little or no ability to adsorb P in a sandy soil. Recently, Jung et al [45] found that among the five different biochars they tested only the biochar derived from peanut shell had good adsorptive capacity because of a proper Ca/P ratio. Apparently, biochar's adsorption capacity largely depends on feedstocks with different mineral compositions.…”
Section: Fundingmentioning
confidence: 99%
“…In addition, the phosphate concentration after mixing PB with only distilled deionized water was also increased up to 3.64 mg L À1 . According to previous reports, the phosphate holding capacity significantly depends on the divalent cation bridging and the ratios of Ca/P and Mg/P in the biochar (Hale et al, 2013;Jung et al, 2015a). As shown in Table 1, the Ca/P and Mg/P ratios of PB were lower than 1.0, which means that PB cannot hold the P content in biochar due to its low ionic strength, and thereby the P content should be released to the aqueous solution.…”
Section: Resultsmentioning
confidence: 84%
“…(2016) [1][2][3][4][5][6][7][8][9][10][11][12] www.deswater.com doi: 10.1080/19443994.2016.1163512 agricultural waste have been used [8][9][10][11][12][13][14]. For instance, activated carbon has been widely recognized as the oldest and most versatile adsorbent used in wastewater treatment to remove diverse organic and inorganic pollutants due to its large specific surface area, high adsorption capacity, porous structure, and good selective adsorption characteristics, which depend on their precursors as well on the synthesis method [15].…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%